2003
DOI: 10.1080/07315724.2003.10719307
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breakfast Type on Total Daily Energy Intake and Body Mass Index: Results from the Third National Health and Nutrition Examination Survey (NHANES III)

Abstract: This analysis provides evidence that skipping breakfast is not an effective way to manage weight. Eating cereal (ready-to-eat or cooked cereal) or quick breads for breakfast is associated with significantly lower body mass index compared to skipping breakfast or eating meats and/or eggs for breakfast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
278
2
15

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(329 citation statements)
references
References 26 publications
34
278
2
15
Order By: Relevance
“…Further, the definition of breakfast consumption was as selfreported by the participants in the study; therefore, it may have varied between them. Yet, this definition is consistent with that used in previous NHANES studies (8)(9)(10)(11) . A misclassification bias may also have potentially resulted if the OB consumers from the present study consumed only a cup of coffee for breakfast, since their energy/ nutrient intakes and metabolism could be different from their OB-consuming counterparts or could be even similar to the BS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Further, the definition of breakfast consumption was as selfreported by the participants in the study; therefore, it may have varied between them. Yet, this definition is consistent with that used in previous NHANES studies (8)(9)(10)(11) . A misclassification bias may also have potentially resulted if the OB consumers from the present study consumed only a cup of coffee for breakfast, since their energy/ nutrient intakes and metabolism could be different from their OB-consuming counterparts or could be even similar to the BS.…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, the use of a single 24 h dietary recall to assess breakfast skipping or breakfast consumption did not permit the assessment of the regular breakfast consumption habits of the population. Nevertheless, a single 24 h dietary recall does produce reasonably robust group estimates of dietary intakes (56) and has previously been used to estimate daily breakfast consumption habits in large data sets such as the NHANES (8)(9)(10)(11) . Also, many times with self-reported dietary assessment techniques such as the 24 h dietary recall, individuals tend to under-report energy intake, especially women and those who are older, overweight or trying to lose weight (57) .…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Breakfast consumption has been suggested to be important for energy regulation; 12,13 however, while some studies have shown a lower percentage of total daily energy intake at breakfast associated with a higher BMI in younger 12 and older 14 persons, others have found no relationship. 13,[15][16][17] Although snacking, usually defined as eating at occasions other than meals (e.g., breakfast, lunch or dinner), is commonly regarded as contributing to excess weight, 18,19 studies on snacking associated with BMI have also yielded mixed results. 15,20,21 One potential explanation for the equivocal findings among studies is dietary reporting bias.…”
Section: Introductionmentioning
confidence: 99%
“…Breakfast consumption is associated with diet quality throughout the day; specifically, those who consume breakfast have higher levels of daily fibre intake (14)(15)(16)(17) , higher vitamin and nutrient intakes (12,(14)(15)(16)18,19) , lower levels of added sugars (16,18) and lower daily percentage of fat (14) . Additionally, numerous studies have shown that breakfast skipping is associated with an increase in overweight, obesity and BMI among adolescents (12,17,(19)(20)(21)(22)(23)(24)(25)(26) .…”
mentioning
confidence: 99%